Molecular characterization, alternative splicing and expression analysis of ACSF2 and its correlation with egg‐laying performance in geese. (8th April 2016) - Yu, S.; Wei, W.; Xia, M.; Jiang, Z.; He, D.; Li, Z.; Han, H.; Chu, W.; Liu, H.; Chen, J.
Summary: ACSF2 (encoded by acyl‐CoA synthetase family member 2 ) belongs to the acyl‐CoA synthetase (ACS) family, activating fatty acids by forming a thioester bond with CoA. In our previous study, a SNP residing in the intron of ACSF2 was identified to be linked to goose egg‐laying performance. But the structure of goose ACSF2 as well as its role in reproduction remains unknown. In this study, we cloned and characterized ACSF2 in Yangzhou geese. A total of four alternative splice variants, designated as ACSF2 ‐1, ACSF2 ‐2, ACSF2 ‐3 and ACSF2 ‐4 respectively, were identified in the ovary. The coding regions of the four variants are 1770, 1692, 1599 and 1917 bp in length, respectively encoding 589, 563, 532 and 638 amino acids with conserved AMP‐binding sites. All ACSF2 variants were widely expressed in 11 tested tissues in geese, except that the ACSF2 ‐2 transcript was not detected in hypothalamus, pituitary gland and granulosa cells. Subcellular localization revealed that ACSF2 is a mitochondrial matrix protein. ACSF2 mRNA level was compared between high egg production (HEP; n  =   8) and low egg production (LEP; n  =   10) groups and showed a lower ( P  <   0.05) mRNA level in the HEP group. Further experiments indicated that overexpressing ACSF2 resulted in a significant increase of caspase‐3 mRNA levels and that ACSF2 knockdown triggered a decrease in the caspase‐3 mRNA level in granulosa cells. Similarly, the lower caspase‐3 mRNA levels were identified in ovaries of the HEP group with lower ACSF2 mRNA levels. The research showed that the ACSF2 mRNA levels had a positive correlation with caspase‐3 mRNA levels in vivo ( R  = 0.86, P  <   0.01). Our results suggest that lower ACSF2 expression promotes the laying performance of goose possibly by inhibiting granulosa cell apoptosis and facilitating follicular development.